Prescaling in a far-from-equilibrium Bose gas - Schmied, Christian-Marcel; Mikheev, Aleksandr N.; Gasenzer, Thomas (Arxiv, 2018)
Non-equilibrium conditions give rise to a class of universally evolving low-energy configurations of fluctuating dilute Bose gases at a non-thermal fixed point. While the fixed point and thus full scaling in space and time is generically only reached at very long evolution times, we here propose that systems can show prescaling much earlier, on experimentally accessible time scales. During the prescaling evolution, some well-measurable short-distance properties of the spatial correlations already scale with the universal exponents of the fixed point while others still show scaling violations. Prescaling is characterized by the evolution obeying already, to a good approximation, the conservation laws which are associated with the asymptotically reached non-thermal fixed point, defining its belonging to a specific universality class. In our simulations, we consider $N=3$ spatially uniform three-dimensional Bose gases of particles labeled, e.g., by different hyperfine magnetic quantum numbers, with identical inter- and intra-species interactions. In this system, the approach of a non-thermal fixed point is marked by low-energy phase excitations self-similarly redistributing towards smaller wave numbers. During prescaling, the full $U(N)$ symmetry of the model is broken while the conserved transport, reflecting the remaining $U(1)$ symmetries, leads to the buildup of a rescaling quasicondensate distribution.